The big deal about Little League ; Changing roles ; Prime time [videorecording] - Lazaro, Cheche (The Probe Team, 1992)
A debate on the controversy of Philippines representatives on Little League International. Looks at surgical sex change among homosexuals. Features also the new and promising talents of onnie Henares Prime Line: Patricia and Tiny.